Is Your Firm Ready for Design Thinking? - Asep Taryana; Dony Hidayat Istiarizqi; Fajar Abhirama A. Ikhsan; Fran Sagita Widodo; Michael Teddy Fernando; Shania Latifa Mirza (Fakultas Ekonomi, Universitas Ichsan Gorontalo, 2022)
To determine the readiness of the company in applying the design thinking process, a measurement is needed. Thus, the company's leadership does not encounter problems in applying design thinking. The research method is based on the framework from Dunne, Eriksson and, Kietzmann on the analysis of company readiness in applying design thinking (DT). The readiness aspect is divided into eight dimensions, namely: goals, collaboration, work style, thought processes, knowledge generation, constraints, failures, and workflow. These eight dimensions are measures in the design thinking readiness matrix which are divided into four quadrants, namely: not ready for DT, ready to encourage DT, ready to fight DT's frustrations, ready to adopt DT. The research was conducted at PT. XYZ to assess readiness to apply DT. The results of this study indicate that PT. XYZ is moving towards the readiness stage to encourage DT. Therefore the leadership of PT. XYZ needs to strengthen the perceptions of managers and employees about design thinking in the company.